Long-term real-life safety profile and effectiveness of fumaric acid esters in psoriasis patients: a single-centre, retrospective, observational study - Dickel, Heinrich; Bruckner, Thomas; Altmeyer, Peter (Journal of the European Academy of Dermatology and Venereology, 2018)
Background Fumaric acid esters (FAEs) are an established systemic treatment for moderate-to-severe psoriasis. However, the long-term clinical safety and effectiveness of continuous FAE monotherapy and combination therapy have not been established. Objective To examine the long-term safety and effectiveness of FAEs as monotherapy and in combination with phototherapy or methotrexate in patients with psoriasis treated at a single centre in Germany. Methods This monocentric, retrospective observational study, with a follow-up period of up to 32.5 years, included 859 patients: 626 received FAE monotherapy, 123 received FAEs with concomitant phototherapy and 110 received FAEs with methotrexate. Results Approximately half of patients (49.0%) reported adverse events (566 total events), most of which involved the gastrointestinal tract. Serious adverse events were reported in 2.3% of patients, but none were deemed to have a causal relationship with any of the treatment regimens. Adverse events leading to treatment discontinuation were observed in 12.9% of patients. A median duration of 1 year was observed in all three treatment subcohorts (P = 0.70) from initiation of FAE treatment to a 50% response rate, where response was defined as achieving a cumulative static Physician's Global Assessment (PGA) score of ‘light’ and at least a 2-point reduction in baseline PGA. A 50% response rate for the cumulative Psoriasis Area and Severity Index 75 was achieved in the FAE monotherapy subcohort after a median of 3 years of treatment, in the FAEs + phototherapy subcohort after 6.7 years and in the FAEs + methotrexate subcohort after 8.1 years (P = 0.001). Conclusion According to our data, FAEs as monotherapy or in combination with phototherapy or methotrexate are safe and beneficial for long-term clinical use. However, multicentre, randomized controlled trials are required to establish the clinical value of monotherapy versus combination therapy and the optimal treatment duration.
Gesehen am 02.03.2020